The Development of Atomic Structures by Dalton, Thomson Rutherford and Bohr, and their Mathematical Equations - Suhaimi, Nurnisaa binti Abdullah; Cahyandari, Rini; Salih, Yasir (Research Collaboration Community (RCC), 2024)
Thomson's atom is a solid ball or billiard ball with a positive charge that contains several negatively charged particles or electrons. These electrons will be spread on the ball like raisins on bread. The main difference between Thomson's and Rutherford's atomic models is that Thomson's model does not contain information about the atomic nucleus, while Rutherford's model does. The theory of atomic structure helps scientists understand why elements behave in certain ways in chemical reactions. For example, electron configuration determines how elements bond and form compounds. In this paper, a literature review was conducted on the development of Thomson's atomic structure model. The study method was carried out to identify elements based on their atomic number, determine their reactivity based on the number of valence electrons, and understand how atoms unite to form molecules through chemical bonds. The results of the study, by studying atomic theory, can find out about the chemical and physical properties, as well as the uses of particles or substances that exist around the universe.